The mediating role of total quality management between human resource practices, information technology infrastructure and performance of Pakistan public hospitals - Maqbool, Muhammad Qasim (Academic Research Publishing Group, 2019)
Health care sector in developing countries is striving for sustainable performance, where total quality management and national culture has considered as a key strategy for the hospitals to become more effective. Although, to understand the diverse perceptions of health care sector performance, this study aims to examine the impact of information technology infrastructure (ITI), human resource management practices (HRM) on the health care sector performance in Pakistan with the mediating effect of total quality management and the moderating role of national culture. However, this research used SmartPLS (SEM) 3.0 for the analysis of survey data (n = 249) collected from doctors working in public hospitals of Pakistan. Empirical results found that from six direct hypothesis,five have a direct strong relationship with total quality management (TQM) and organization performance (OP). Where, total quality management mediates the relationship between HRM and organization performance except ITI. Finally, national culture moderated the relationship between TQM and organization performance.